2006
DOI: 10.1073/pnas.0600651103
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocytes kill multiple targets simultaneously via spatiotemporal uncoupling of lytic and stimulatory synapses

Abstract: A longstanding paradox in the activation of cytotoxic T lymphocytes (CTL) arises from the observation that CTL recognize and rapidly destroy target cells with exquisite sensitivity despite the fact that cytokine production requires sustained signaling at the immunological synapse. Here we solve this paradox by showing that CTL establish sustained synapses with targets offering strong antigenic stimuli and that these synapses persist after target cell death. Simultaneously, CTL polarize lytic granules toward di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
150
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(175 citation statements)
references
References 29 publications
17
150
0
5
Order By: Relevance
“…Cytotoxicity can be induced in CD8 + T cells at low antigen concentrations or after rapid TCR-pMHCI interactions, while cytokine production requires relatively high antigen concentrations and a significantly longer duration of TCR ligation [33][34][35]. Thus, it is not altogether surprising that differences in the kinetics of TCR dissociation between epitope-specific CD8 + T cell populations, as observed in this study, might lead to differences in cytokine profiles.…”
Section: Discussionmentioning
confidence: 57%
“…Cytotoxicity can be induced in CD8 + T cells at low antigen concentrations or after rapid TCR-pMHCI interactions, while cytokine production requires relatively high antigen concentrations and a significantly longer duration of TCR ligation [33][34][35]. Thus, it is not altogether surprising that differences in the kinetics of TCR dissociation between epitope-specific CD8 + T cell populations, as observed in this study, might lead to differences in cytokine profiles.…”
Section: Discussionmentioning
confidence: 57%
“…For cytotoxic effectors, E, killing an exponentially growing pathogen, one can easily see that effector/ target ratios should play an important role. CTLs cannot kill an infinite number of infected target cells per day because it takes time to locate and bind them, to deliver a lethal hit, and to dissociate to find the next target cell (66,89,97). This "handling time" creates a saturation effect similar to that of Michaelis-Menten enzyme-substrate kinetics (16,26,76).…”
Section: Resultsmentioning
confidence: 99%
“…Asquith et al (6) estimated that CTLs specific for human T-lymphotropic virus type 1 (HTLV-1)-infected cells kill no more than five target cells per day. Stinchcombe et al (89) and Wiedemann et al (97) showed that CTLs kill the target cells that they are associated with in a few minutes. Two-photon microscopy studies suggest that CTL killing takes about half an hour (66).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the need for stable IS for target-cell killing has been questioned by the observation that low levels of antigen on APCs stimulate Fasmediated CTL killing without formation of stable Kupfer-type IS (19)(20)(21). Thus, the function of stable IS induced by higher antigen levels may be related more closely to perforin-mediated cytotoxicity (20) and/or cytokine secretion (15,22). In addition to these in vitro studies, we and others have described SMACs in T cells in vivo, and the resulting cellular reorganization in "postsynaptic" target cells during the effector phase of an antiviral immune response (14-16, 25, 24) and in human brain tumors (17).…”
mentioning
confidence: 99%